Adults referred to the ADHD clinic in Iceland : clinical characteristics - Bára Sif Ómarsdóttir 1991- (2017)
Objective: To explore the characteristics of adults referred to the ADHD clinic at Landspitali-The National University Hospital of Iceland from 2013 to 2015 (N=531) and compare those who did not meet screening criteria (N=136), those who did not meet diagnostic criteria for ADHD (N=90) and those who met diagnostic criteria (N=305). Method: Data was obtained from the participants’ medical files which included scores on the ADHD Rating Scale, background information, information from the MINI diagnostic interview and a number of psychological scales (the Depression Anxiety Stress Scales, the Clinical Outcome of Routine Evaluation – Outcome Measure, the Beck Depression Inventory II and the Beck Anxiety Inventory). Results: ADHD diagnosis was associated with lower educational status and more parental and teachers concerns about development and behaviour in childhood. Participants with ADHD also reported more ADHD symptoms on the ADHD Rating Scale, both in childhood and adulthood, compared to the other two groups. The participants who did not meet diagnostic criteria for ADHD had more current psychopathology; 50% had two or more other psychiatric disorders, compared with 35.5% of the participants with ADHD. No significant differences appeared between the two groups on the psychological scales (DASS, CORE-OM, BDI-II and BAI). Conclusion: Adults referred to the ADHD clinic at Landspitali have multiple problems, regardless of whether they get ADHD diagnosis or not. Clinicians therefore need to be attentive of the adults who are referred to the ADHD clinic but do not meet diagnostic criteria. Keywords: Attention Deficit Hyperactivity Disorder; Adult ADHD; General characteristics; Psychological wellbeing; ADHD Rating Scale